1988
DOI: 10.1099/0022-1317-69-7-1497
|View full text |Cite
|
Sign up to set email alerts
|

The N and C Termini of the Coat Proteins of Potyviruses Are Surface-located and the N Terminus Contains the Major Virus-specific Epitopes

Abstract: SUMMARYMild proteolysis by trypsin of particles of six potyviruses (bean yellow mosaic virus, clover yellow vein virus, Johnson grass mosaic virus, passion-fruit woodiness virus, potato virus Y and watermelon mosaic virus II) revealed that the N-and C-terminal regions of their coat protein are exposed on the particles' surfaces. The enzyme treatment removed the N-terminal region (30 to 67 amino acids long, depending on the virus) and 18 to 20 amino acids from the C terminus of the coat proteins, leaving a full… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
241
2
5

Year Published

1989
1989
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 281 publications
(267 citation statements)
references
References 41 publications
15
241
2
5
Order By: Relevance
“…Most of the differences (including a 16 residue deletion in SMV-N) occurred in the 45 N-terminal residues, with the remainder of the two coat protein molecules being very similar (92 ~ homology). This observation, that the 235 C-terminal amino acid residues are far more conserved than the surface-exposed, immunodominant N-terminal region (Shukla et al, 1988b), suggested that the 3' end of the potyvirus genome including the untranslated region may be an accurate marker of genetic relatedness.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the differences (including a 16 residue deletion in SMV-N) occurred in the 45 N-terminal residues, with the remainder of the two coat protein molecules being very similar (92 ~ homology). This observation, that the 235 C-terminal amino acid residues are far more conserved than the surface-exposed, immunodominant N-terminal region (Shukla et al, 1988b), suggested that the 3' end of the potyvirus genome including the untranslated region may be an accurate marker of genetic relatedness.…”
Section: Discussionmentioning
confidence: 99%
“…VCD has provided evidence for helical structures in all of the viruses and some b-sheet structures in PVX, NMV and PMV, but not in TMV. It has been suggested (Sawyer et al, 1987;Shukla et al, 1988; Blanch et al, 2002) that the coat protein folds of PVX and NMV may be similar to that of TMV, being based on the helix bundle, but with differences in detail resulting from differences in the appended loops and turns and from the extra sequences present in the potexviruses. These differences may be responsible for the observed VCD differences.…”
mentioning
confidence: 99%
“…According to predicted CP masses of plant viruses (Blouin et al, 2009), most virus CPs have masses lower than Rubisco, although some fall within its mass range. Another consideration is that viral CPs can be resistant to trypsin digestion because of post-translational modification (Shukla et al, 1988), which may explain why coverage of tryptic fragments of viral CPs was relatively low (11-36%). It is worth noting that viral proteins other than CPs were not observed on the gels or detected by PMF, probably because they were in quantities below the resolution of the Coomassie stain used.…”
mentioning
confidence: 99%